Ann Snitow meets Czech feminists - Smidova, Iva; Vodochodsky, Ivan (Gender, Equal Opportunities, Research, 2015)
Ann Snitow, Professor of Literature and Gender Studies at the New School in New York City, is known for her love and passion for travelling feminism. She has been an outstanding supporter of Czech feminists and one of the core enthusiastic representatives of thematic East-West feminist debates. Book grants from the Network of East-West Women, of which she is a co-founder, significantly cultivated feminist endeavours after 1989 in the Czech context and beyond.Ann Snitow has been a feminist activist since 1969. She was a founding member of New York Radical Feminists and for six years was Director of the Gender Studies Program at the New School. She has been engaged in shaping the direction of feminist debates on sexuality (Powers of Desire: The Politics of Sexuality, 1983), taking a critical standpoint towards censorship, defending the right to one's fantasies, and, most of all, advocating for diversity and openness while provoking radical questions